Between Mystery and Riddle: From Narrative Strategy to Literary Genre - Fedunina, Olga (Slavica, 2018)
In the paper a difference is made between the mysterious and the enigmatic as fundamentally different narrative and genre strategies. The first is typical of the so-called novelmystery or the novel-myth, charcterized by the concept of impossible rational comprehension of the mystery explained by the plot. The second represents a vast field of criminal literature, where the plot is dependent on a riddle that has a pre-given answer. The differences between these two types of novels are manifested at all the main levels of poetics, especially in the specific traits of the subject-oriented organization. However, the paper shows that the general strategy of the mysterious is also implemented through different moods in different criminal genres such as classic detective stories, the police novel, the “adventurous investigation”, and the “victim-centered investigation”. Thus, we can conclude that the mystery and the riddle can reassemble genre constructive strategies not minus then narrative.